The effect of teaching English using virtual classrooms on developing creative thinking skills for primary school students in Makkah - Al-Harbi, Sarah Fahad (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the effect of teaching English using virtual classrooms on developing creative thinking skills among primary school students in Makkah. To achieve the objectives of the study, the researcher used the semi-experimental approach in the experimental and control group system, and the study was applied to a sample of (50) students. An experimental group (25) students is divided into two groups, for whom he is taught using the virtual classroom strategy, and a control group (25) students is taught for them in the traditional way, and the study showed the presence of statistical significance at the level of significance (a = 0.05). The difference between the mean scores of the two groups' students in the post application of the creative thinking test for the skill (fluency- originality- flexibility) and for the benefit of the experimental group, which was studied using virtual classes. Based on the results of the study, the researcher recommended encouraging English language teachers to use virtual classrooms in teaching, and conducting other studies on the effect of using virtual classrooms on other variables.
Keywords: Virtual Classroom; English Language; Creative Thinking; Makkah Al-Mukarramah